Effects of Alternating Bilateral Training Between Non-Paretic and Paretic Upper Limbs in Patients with Hemiparetic Stroke: A Pilot Randomized Controlled Trial - Masashi Kumagai; Shintaro Uehara; Taichi Kurayama; Shin Kitamura; Sachiko Sakata; Kunitsugu Kondo; Eiji Shimizu; Naoki Yoshinaga; Yohei Otaka (Medical Journals Sweden, 2022)
Objective: To examine whether alternating training with both the non-paretic and paretic sides (alternating bilateral training), expecting trial-to-trial inter-limb transfer of training effects from the nonparetic to the paretic side, improves upper-limb motor performance in post-stroke patients, compared with unilateral training involving only the paretic side. Design: An assessor-blinded pilot randomized controlled trial. Subjects: Twenty-four right-handed post-stroke patients with hemiparesis. Methods: Participants were randomly allocated to either an alternating bilateral training group or a unilateral training group (n = 12/group). Participants underwent dexterity training of the paretic arm using the Nine-Hole Peg Test, completing 10 trials/day for 7 consecutive days. The alternating bilateral training group additionally performed alternating trials with the non-paretic limb. Performance change, assessed 1 day and 1 week after the 7-day training period, was compared between groups. Results: Although the improvement was comparable in both groups at both post-training time-points, a sub-analysis in which those with left hemiparesis and those with right hemiparesis were analyzed separately revealed potential benefits of the alternating bilateral training, specifically for those with left hemiparesis. Conclusion: Alternating bilateral training may augment training effects and improve upper-limb motor function in patients with left hemiparesis. LAY ABSTRACT Post-stroke patients often experience long-term impairments affecting dexterity and motor control of the paretic upper limb. Recent studies have suggested that a unique training method, based on the inter-limb transfer phenomenon, expecting transfer of the training effect of the trained to the contralateral limb, has the potential to improve the performance of the paretic side. However, this traditional model focuses on training only with the non-paretic side, and thus cannot be directly applied to clinical settings. This study developed and evaluated the effect of a new clinically relevant strategy in which post-stroke patients underwent alternating training of the upper limbs of the non-paretic and paretic sides. Although the training effect was comparable with that of the unilateral training involving only the paretic side, a sub-analysis revealed a potential benefit of the alternating training specifically for left hemiparetic patients. The proposed training strategy could help post-stroke patients improve upper-limb motor function.